A Framework for Managing Currency Risk and Exchange Rate Exposure in International Energy Investment Portfolios - Wasiu Eyinade; Onyinye Jacqueline Ezeilo; Ibidapo Abiodun Ogundeji (International Journal of Scientific Research in Civil Engineering, 2022)
The globalization of energy investment has intensified exposure to currency risk, posing significant challenges to the valuation, financing, and performance of international energy portfolios. This paper presents a conceptual framework for identifying, assessing, and managing currency risk within the context of cross-border energy investments. It begins by distinguishing the principal forms of currency exposure—transaction, translation, and economic—and explains their specific manifestations across the upstream, midstream, and downstream segments of the energy sector. The framework integrates sensitivity analysis, scenario planning, financial derivatives, and natural hedging strategies into a cohesive approach that can be tailored to diverse portfolio structures and market conditions. It further embeds risk management within organizational governance, ensuring alignment with long-term investment objectives. By applying the framework to the energy sector’s unique characteristics—capital intensity, extended time horizons, and multi-currency revenue streams—the paper offers strategic insights for investors, fund managers, and policymakers. It concludes with recommendations for building more resilient energy investment practices and highlights directions for future empirical and interdisciplinary research.
Keywords: Currency Risk; Exchange Rate Exposure; Energy Investment; Risk Management Framework; International Portfolio Management; Hedging Strategies